DESAIN SIPUTMATIKA DAN RANCANGAN LINTASAN BELAJAR SISWA SEKOLAH DASAR PADA MATERI SIMETRI PUTAR - Zuliana, Eka (Refleksi Edukatika : Jurnal Ilmiah Kependidikan, 2017)
The purposed of this research is to get the design of siputmatika and the design of learning trajectory of mathematics for rotary symmetry material. Siputmatika is a device that can help students to construct rotary symmetry. This device can be modified by elementary school students to build the concept, prove and be a tool in making learning trajectory of rotary symmetry. This research is a design research with pre eliminary design as the first stage. The literature review and study of concepts and appropriate media are used to design siputmatika. The result of this research is the design of learning trajectory for rotary symmetry material. Hypothetical learning trajectory is expected to be a tool and signs for the elementary school teachers in conducting learning process to help students construct their own concept of rotary symmetry using siputmatika.